Hubungan Pemakaian Alat Kontrasepsi Dalam Rahim (AKDR) Non Hormonal dengan Kejadian Vaginitis - Sari, Eka Mega; Prawitasari, Shinta; Attamimi, Ahsanudin (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2018)
Background: Colonies of microorganism in reproductive normal women vaginal is influenced by several factors. Changes in the composition of these factors cause of some problems such as infection and inflammation. The use of intrauterine devices could be expected to lead to vaginitis.Objective: To determine whether the use of intrauterine device increase the incidence of vaginitis, either by Bacterial Vaginosis (BV), Vulvovaginal Candidiasis (VVC), and Trichomonas Vaginalis (TV) .Method: Cross Sectional Study on the differences incidence of vaginitis in intrauterine device user and hormonal user.Result and Discussion: At the intrauterine devices and hormonal contraception users, there are significant difference incidence of BV (OR 10,11;95% CI 1,80-56,78) ; p=0,009 (p<0,05) dan VVC (OR 29,78 (1,64-2540,69); p=0,022 (p<0,05), but not TV (OR 3,68;95% CI 0,11-117,63); p=0,460 (p>0,05).Conclusions: The use of an intrauterine device increase the incidence BV and VVC but not Â TV.Keywords: Intrauterine Device; Hormonal Contraception; Vaginitis